Bovine alloreactive cytotoxic T cells - Teale, A.J.; Morrison, W. Ivan; Spooner, R.L.; Goddeeris, Bruno M.; Groocock, C.M.; Stagg, D.A. (Cambridge University Press, 1986)
The target antigens recognized by bovine alloreactive cytotoxic T cells are discussed and compared with serologically defined bovine major histocompatibility complex (MHC) products which make up the bovine lymphocyte antigen (BoLA) system. The role of MHC products in T-cell function in other species is reviewed with particular emphasis on the use of cytotoxic T cells in the characterization of human and murine MHC products and in the Development of cytotoxic T-cell technology in general. In the bovine system, serologically defined BoLA-A-locus products w8 and w11 are closely associated with, or identical to, the target determinants for cytotoxic T cells generated in vitro in peripheral blood mononuclear cells (PMB) of unprimed w8- and w11-negative cattle cocultured with w8/w11 PMB. There was little evidence of cytotoxicity directed against other products of the MHC. In similar studies of the specificity of cytotoxic T cells generated against PMB carrying the serologically defined specificity w6 and its subgroups, cytotoxicity could be detected with correlated with distribution of the subgroups of w6 on target cells, but not with w6 itself. The generation and specificity of cytotoxic T cells in cocultures of w8/w11 responder PMB and w8/w11 stimulator PMB were also examined. In some cases, cytotoxic T cells were generated and their target specificity suggested that products of a second cell-mediated lympholysis-controlling locus in cattle were being detected. The nature of these products is not known.